2020
DOI: 10.1515/med-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1 promotes LPS-induced inflammatory injury in macrophages by regulating miR-17-5p/TLR4

Abstract: AbstractBackgroundThe inflammatory response of macrophages is responsible for sepsis. Long noncoding RNA nuclear enriched abundant transcript 1 (NEAT1) has been reported to be involved in sepsis development. However, its underlying mechanism remains largely unclear. This study aims to investigate the effect of NEAT1 on inflammatory response of macrophages and explore the regulatory networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Silencing of circTLK1 attenuated myocardial ischaemia/reperfusion injury by sponging miR‐214 17 . Up‐regulation of miR‐17‐5p suppressed inflammation in sepsis, which was suggested as a therapeutic target for sepsis 53 . In the current study, the complementarity between circTLK1 and miR‐17‐5p was predicted by bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 67%
“…Silencing of circTLK1 attenuated myocardial ischaemia/reperfusion injury by sponging miR‐214 17 . Up‐regulation of miR‐17‐5p suppressed inflammation in sepsis, which was suggested as a therapeutic target for sepsis 53 . In the current study, the complementarity between circTLK1 and miR‐17‐5p was predicted by bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 67%
“…These results demonstrated the therapeutic effects of noni fruit juice on acute gouty arthritis in mice. Furthermore, studies have shown that other four miRNAs (i.e., miR-122-5p, miR-146a-5p, miR-17-5p, and miR181c-5p) are involved in uric acid nephropathy, acute pneumonia, LPS-induced inflammatory injury, and poststroke inflammation, by combining with long noncoding RNAs of ANRIL, SNHG16, NEAT1, and Malat1, respectively [ 26 , 28 , 33 , 82 ]. Similarly, our results showed that these four miRNAs responded to the treatments of noni fruit juice and colchicine, showing up- and downregulated expressions in model mice and mice treated with both noni fruit juice and colchicine, respectively, indicating the therapeutic effects of noni fruit juice on acute gouty arthritis in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, NEAT1 is not only im-plicated in cancer, but may also affect the inflammatory response. Li et al (35) reported that NEAT1 may promote LPS-induced inflammatory injury in macrophages by regulating miR-17-5p/TLR4. In addition, downregulation of NEAT1 promoted cell proliferation and inhibited the apoptosis of rat cardiac muscle cells (36).…”
Section: Discussionmentioning
confidence: 99%